HUMAN VALUES AND ATTITUDES TOWARDS MONEY - Muzikante, Inese; Škuškovnika, Daina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2018)
Spending money which is not earned becomes more available practice with help of the various types of cash loans. It causes social problem in society because easiness of getting money puts families at risk due to the high loan percent. Our study aims to understand ifhuman values are related to attitudes towards money and in what way if any.Values are motivational constructs that apply to abstract goals (Schwartz, 1992). Schwartz believes that the main aspect of value contents is the type of goal or the motivation it expresses (Schwartz, 1992). Also, values are abstract goals and do not effect decisions in specific situations they can work as the underlying assumptions for creating attitudes. Attitudes are more situation-specific and correlate with behavior at moderate level. In our study values were measured using Portrait Values Questionnaire, PVQ-21 (Schwartz, Melech, Lehmann, Burgess, & Harris, 2001). Attitudes towards money were measured using modified version of Money Attitude Scale (Yamauchi & Templer, 1982). Question regarding money related behavior were also asked. We surveyed one thousand and five respondents from whom 58% were female, all age groups where presented according to Latvia’s population (representative sample). Results reveal that values correlate with attitudes towards money although modestly.